PLGA/BK microspheres targeting the bradykinin signaling pathway as a therapeutic strategy to delay intervertebral disc degeneration - Xiaoming Qiu; Yizhi Zhang; Ziyan Wei; Zhangbin Luo; Zhuanping Wang; Xuewen Kang (Communications Biology)
Abstract Intervertebral disc degeneration(IVDD) is a common spinal condition with limited effective treatments available. This study aims to investigate the impact of poly(lactic-co-glycolic acid)/Bradykinin (PLGA/BK) microspheres on IVDD and its underlying mechanisms. We collected nucleus pulposus samples from both healthy and degenerated human intervertebral disks and conducted immunohistochemical analyses, revealing reduced BK expression in degenerated tissues. Subsequently, we used BK to treat nucleus pulposus cells and conducted Bulk RNA sequencing (RNA-seq), identifying BK’s involvement in cellular senescence, extracellular matrix metabolism, and the PI3K signaling pathway. Further experiments using tert-butyl hydroperoxide (TBHP)-induced cell senescence showed that BK treatment reduced senescence, enhanced extracellular matrix synthesis, and inhibited degradation, along with activation of the PI3K pathway. These effects were mediated through B2R (BK receptor 2) and the downstream PI3K pathway. Following this, we developed sustained-release BK microspheres with an optimized manufacturing process. In vitro co-culture experiments showed no observable toxicity. We established an IVDD model in rat tail vertebrae through fine needle puncture, administering local injections of BK sustained-release microspheres. Using various experimental methods, including X-ray, MRI, histopathology, and immunohistochemistry, we found that these microspheres could slow the progression of IVDD. This study highlights the potential of injectable PLGA/BK microspheres to regulate cellular senescence and extracellular matrix metabolism via the B2R and PI3K pathways, ultimately delaying IVDD.